Sistem knjižničnega nadomestila v Sloveniji - Pirš, Simon (Knjižnica, 2015)
The article deals with the issue of the efficiency of the Slovenian public lending right system. We assessed the system through a comparison with international public lending right systems. First we analysed each system and then compared them to each other on the basis of the core characteristics of PLR systems according to the European Union Directive 92/100/EEC. We compared the mechanisms of Denmark, France, Germany, Australia and Slovenia. Besides the substantive comparison, we also tried to compare them statistically, according to available data. Analysis showed that the Slovenian system can be considered efficient on the international scale. The research of this topic is difficult due to the unavailability of relevant data. The research is useful because it illuminates the problems of the Slovenian PLR system and it is topical and current because it touches upon topics in PLR on which Javna agencija za knjigo is considering making changes.
Keywords: knjižnično nadomestilo; public lending right; cultural policies; kulturna politika; avtorsko pravo; copyright